Upaya Meningkatkan Pengetahuan Ibadah Shalat melalui Media Gambar dengan Papan Planel di TK Widyatama Cabak Tlogowungu Pati - Yulianawati, Endah (Indonesian Journal of Islamic Early Childhood Education, 2017)
This study aims to determine the increase of studentsâs worship knowledge at TK Widyatama Cabak Tlogowungu Pati through picture and planel board media. Classroom Action Research was conducted in the first semester of the academic year 2016/2017. This research will be carried out in 2 cycles. The analysis is done by using data reduction, display data and conclusion drawing / verification. The results showed that the picture and planel board media can improve the knowledge of the students prayer worship. This is shown from the observations of pre cycle, cycle I, and cycle II. In pre cycles, knowledge of worship in the category of good worship as many as 7 students (23%) and sufficient category as many as 24 students (77%). In the first cycle, the knowledge of worship in the category of excellent students as much as 17 students (55%), good category 11 students (35%), and enough category sebanya 3 students (10%). In the second cycle, the knowledge of worship of the students reaches an increase of 87%, that is very good category as many as 27 students (32%), good category as many as 3 students (10%), and enough category as 1 student (3%). So in cycle II there is still one student who still need guidance from the teacher.